Magnitude of consistent condom use and associated factors among people living with HIV/AIDS in Ethiopia: Implication for reducing infections and re-infection. A systematic review and meta-analysis. - Firomsa Bekele; Lalise Tafese; Teshome Debushe (PLoS ONE)
Background The human immune virus or acquired immune deficiency syndrome, is a major threat to the health of millions of people worldwide. In Ethiopia, there were more than a million people living with HIV/AIDS. The continuous and appropriate use of condoms, particularly among those who have HIV-positive clients, is essential to a comprehensive and long-term approach to avoiding HIV and other STIs as well as unintended pregnancy. But irregular condom use is regularly reported. There is inconsistent reports of the prevalence and correlates of frequent condom use in Ethiopia. This study's goal is to provide an overview of the most recent research on magnitude condom use among people living with HIV in Ethiopia. Methods Four databases of PubMed, Science Direct, Scopus, and Google Scholar were used. Finally, 10 studies that satisfied the eligibility criteria were included in the systematic review and meta-analysis. The data were collected using a methodical checklist for data extraction, and STATA 14 was utilized for the analysis. The consistent condom use was reported as use of condom in every sexual encounter preceding the study. The prevalence of consistent condom usage among HIV/AIDS patients was calculated by dividing the total number of patients who regularly used condoms by the total number of HIV/AIDS patients and multiplying that result by 100. The factors associated with a consistent use of condom were described using the pooled odds ratio (OR) and calculated based on binary outcomes from the included primary studies. The statistical significance was determined based on the correlation factor as their confidence level should not include 1. Subgroup analyses by region and publication years were carried out by using a random-effects model. The STATA commands of metan magnitude semagnitude, random xlab(.1,5,10) lcols (authors) by (variables)texts(120) xsize(18) ysize (14) were used to carried out the subgroup analysis. To assess the presence of publication bias, funnel plot, Egger test and Begg's test at 5% significant level were computed. The asymmetry of funnel plot and the Egger test and Begg's test P value of 0 >0.5 showed the absence of publication bias. The Cochrane Q test statistic and I2 tests were used to assess heterogeneity. Result The pooled magnitude of consistent condom use was 50.56% (95%CI: 38.09-63.02). The predictors of consistent condom use includes urban residence (AOR = 3.46; 95% CI: 2.24-5.35), marital status (AOR = 0.33; 95% CI: 0.18-0.61), and HIV disclosure status (AOR = 5.61;95%CI: 2.29-13.73). Conclusion Half of the HIV/AIDS patients in our study regularly used condoms. According to this study, urban residency, disclosure status, and marital status were all associated with consistent condom use among HIV/AIDS patients. Therefore, health education about condom use should be provided to married couples and people living in rural regions. In addition, disclosing HIV status and the necessity of constant condom usage would be crucial for consistent condom use.